Asian Financial Crisis : a critical study. - Chua, See Joo. (2008)
This study aims to explore the aftermath of the 1997 Asian financial crisis on East Asian economies. Subsequently, this report aims to investigate the failings of the East Asian Economic Development Model and the inability of the East Asian countries to predict the arrival of the financial crisis. Additionally, comparisons are also made between the East Asian financial crisis and the malaise that Mexico suffered in 1994.